Functional development of preterm infants: an integrative literature review - Rayla Amaral Lemos; Maria de La Ó Ramallo Veríssimo
Abstract Introduction: Prematurity is a public health problem. Despite many studies that aim to characterize the effects of premature birth on the various dimensions of child development, there is still little systematic evidence on the functional dimension. Objective: To characterize the functional development of preterm infants in early infancy. Methods: Searches were conducted in PubMed, Science Direct, Scopus, Cochrane, Joana Briggs Institute, Embase, Lilacs and SciELO databases, with the following key words in English and Portuguese and their combinations: preterm, functional performance, functional outcomes, functional limitations, functional skills, activities of daily living and disability. Inclusion criteria were articles published in the last seven years on the investigated subject. Results: The five articles in the sample were organized, analyzed and categorized, reaching up to three empirical categories of analysis: Functional Performance of Preterm, Cumulative Effects on Functional Development, and Environmental Context and Attitudes of Care. Conclusion: It was concluded that before age 6, children born premature have developmental delays in functional areas of self-care, mobility and social function. Their functional development suffers cumulative effects of various different factors and may be related to care practices and context.